Rsk2 controls synovial fibroblast hyperplasia and the course of arthritis. Issue 2 (20th November 2014) - Derer, Anja; Böhm, Christina; Grötsch, Bettina; Grün, Joachim R; Grützkau, Andreas; Stock, Michael; Böhm, Sybille; Sehnert, Bettina; Gaipl, Udo; Schett, Georg; Hueber, Axel J; David, Jean-Pierre
Abstract : Objective: Arthritis is a chronic inflammatory disease characterised by immune cell infiltration and mesenchymal cell expansion in the joints. Although the role of immune cells in arthritis is well characterised, the development of mesenchymal cell hyperplasia needs to be better defined. Here, we analysed the role of the ribosomal S6 kinase Rsk2, which we found to be highly activated in joints of patients with arthritis, in the development of mesenchymal cell hyperplasia. Methods: We genetically inactivated Rsk2 in the tumour necrosis factor (TNF)-α transgenic ( TNF tg) mice, an animal model for human inflammatory arthritis. Clinical and histological signs of arthritis as well as molecular markers of inflammation and joint destruction were quantified. Fibroblast-like synoviocytes (FLS) were characterised in vitro and the effect of Rsk2 deletion on the pattern of gene expression was determined. Results: Rsk2 deficiency in TNF tg mice results in earlier and exacerbated inflammation as well as increased bone and cartilage destruction. The production of inflammatory cytokines, matrix metalloproteinases and osteoclastogenic molecules was significantly increased in vivo upon Rsk2 inactivation. Bone marrow deficient in Rsk2 could not transfer this phenotype, indicating that Rsk2 expression in mesenchymal cells controls the course of arthritis. Indeed, Rsk2 deficiency was associated with a more activated phenotype and higher proliferative capacity of FLS, thereby increasing cytokines and production of matrix proteinases. Conclusions: Rsk2 emerges as a key regulator of mesenchymal cell numbers in the joint and thereby could be targeted to control the inflammatory and tissue-destructive feature of joints in arthritis.